Yeah Baby, yeah! A case study of a film’s “shagadellic” transition into Italian as packaged on a DVD - Crosato, Romina Lerina (My University, 2006)
This paper analyses the decisions made in the dubbing of a comedy of a specific genre, that is, in the translation of the humour used in the English film Austin Powers, The Spy Who Shagged Me into Italian Austin Powers, La Spia Che Ci Provava as packaged on a DVD. The study attempts to answer the following question: Does the dubbing of a film diminish the humourous appeal of the film?
Master of Arts - Translators and Interpreters
Keywords: italian; translation